P158 End of life care for lung cancer; can we identify those in need of support. (2nd December 2011) - Jones, S M; Gallagher, J; Sweeney, T; Pugh, E; McIver, A; Kelly, V; Walshaw, M J; Ledson, M
Abstract : Introduction and Objectives: The End of Life Care Strategy advocates the identification and support of patients approaching the end of their lives, and to aid this, social care benefits can be awarded to those with a life expectancy <6 months by completion of a DS1500 form. Many lung cancer patients fall into this category: we wished to look at the use of this enhanced support mechanism in our busy lung cancer unit. Method: We looked at the use of DS1500 in the initial period for 100 consecutive outpatients with lung cancer diagnosed through our rapid access clinic in 2007 (mean age 73 years [SD 8], mean PS=2 [IQR 2], 47 females), comparing its use with survival and histological tumour type. Mortality data were obtained from the national registry. Results: Twenty two had a DS1500 completed (median 26 days [20] from presentation): there was no difference in age, sex or PS between these and the remainder. Of the 75 with a tissue diagnosis, only those with non-small cell cancer were more likely to receive a form (16/22 vs 30/78 χ 2 =8.1, p=0.004). Only three patients with a clinical diagnosis and three with small cell received forms (both p=NS). Overall median survival was 216 days [IQR 405], with 57 alive at 6 months and 33 at 1-year. Median survival was 193 [268] days for those with DS1500 compared with 224 [458] in the remainder (p=NS), and 31 (57%) of those who died within 6 months did not benefit from early DS1500 status. Conclusion: While the DS1500 use was appropriate, the number identified represented less than a half of those who died within 6 months of presentation, and those with the poorest prognosis (small cell type or a clinical diagnosis) did not benefit the most. It seems we are missing an opportunity to support this unfortunate group of patients at the time of their greatest need.